Four Psychosocial Dimensions Of Child Laborers In Pakistan - Shahid, Zakia (2023)
This study provides insight into the psychosocial dimensions of child laborers in Pakistan. Child labor is a significant problem in many developing countries. Pakistan is the most severe example of a country grappling with the issue of child labor. The objective of the study is to investigate four psychosocial dimensions: mental, emotional, spiritual, and social adjustment, among child laborers. Child labor deprives children of their childhood and self-esteem, negatively affecting their overall development. To investigate the research problem, a qualitative study was applied to explore the perceptions of all participants from three different groups, including child laborers, parents of child laborers, and top management of child labour institutes, about the influences of child labor activities on their psychosocial development. Purposive sampling was used to collect data, and semi-structured interviews were carried out. NVivo 12 was used to analyze data. The trustworthiness of the coding process is achieved through data triangulation. The findings indicate that child labor has predominantly negative effects on the psychosocial development of children in Pakistan. It emphasizes the need for quality education to foster positive psychosocial development among child laborers, parents and the educational system playing essential roles. The study identifies four psychosocial dimensions (rational, emotional, social, and spiritual) impacted negatively by child labor, resulting in an imbalance in the psychosocial development of child laborers. Future research should explore effective interventions and policy strategies to support and protect child laborers across these dimensions.